2010
DOI: 10.1089/jpm.2009.0245
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Challenges in Use of a Standardized Symptom Assessment Instrument in Hospice

Abstract: Background: Hospices are now mandated to perform routine quality assessment under the final Medicare Hospice Conditions of Participation, creating an opportunity to explore standardized approaches to monitoring hospice quality. Objective: We report hospice staff experiences using a standardized symptom assessment instrument, the Edmonton Symptom Assessment System (ESAS), in a pilot study designed to develop and test quality measures on symptom management. Use of the ESAS illustrates the benefits and challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Previously reported concerns from HCPs have focused on four key areas: (a) clinical relevancy [28], (b) misunderstandings regarding appropriate use [15,29], (c) misinterpretation of high symptom ratings as poor quality of care [15], and (d) attitudinal barriers [15,28]. Some HCPs have suggested that the tool lacks clinical relevancy if other team members do not refer to the tool when deciding about treatment options [28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously reported concerns from HCPs have focused on four key areas: (a) clinical relevancy [28], (b) misunderstandings regarding appropriate use [15,29], (c) misinterpretation of high symptom ratings as poor quality of care [15], and (d) attitudinal barriers [15,28]. Some HCPs have suggested that the tool lacks clinical relevancy if other team members do not refer to the tool when deciding about treatment options [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some HCPs have suggested that the tool lacks clinical relevancy if other team members do not refer to the tool when deciding about treatment options [28]. Others have highlighted concerns regarding the lack of understanding regarding the tool's use, particularly with respect to frequency of assessments and the misinterpretation of numerical rating scales [15,29]. In one study [15], participants reported concerns about high symptom ratings being interpreted as poor quality of care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations